Removing carbon catabolite repression in Parageobacillus thermoglucosidasius DSM 2542 - Liang, Jinghui; van Kranenburg, Richard; Bolhuis, Albert; Leak, David J. (Frontiers in Microbiology, 2022)
Parageobacillus thermoglucosidasius is a thermophilic bacterium of interest for lignocellulosic biomass fermentation. However, carbon catabolite repression (CCR) hinders co-utilisation of pentoses and hexoses in the biomass substrate. Hence, to optimise the fermentation process, it is critical to remove CCR in the fermentation strains with minimal fitness cost. In this study, we investigated whether CCR could be removed from P. thermoglucosidasius DSM 2542 by mutating the Ser46 regulatory sites on HPr and Crh to a non-reactive alanine residue. It was found that neither the ptsH1 (HPr-S46A) nor the crh1 (Crh-S46A) mutation individually eliminated CCR in P. thermoglucosidasius DSM 2542. However, it was not possible to generate a ptsH1 crh1 double mutant. While the Crh-S46A mutation had no obvious fitness effect in DSM 2542, the ptsH1 mutation had a negative impact on cell growth and sugar utilisation under fermentative conditions. Under these conditions, the ptsH1 mutation was associated with the production of a brown pigment, believed to arise from methylglyoxal production, which is harmful to cells. Subsequently, a less directed adaptive evolution approach was employed, in which DSM 2542 was grown in a mixture of 2-deoxy-D-glucose(2-DG) and xylose. This successfully removed CCR from P. thermoglucosidasius DSM 2542. Two selection strategies were applied to optimise the phenotypes of evolved strains. Genome sequencing identified key mutations affecting the PTS components PtsI and PtsG, the ribose operon repressor RbsR and adenine phosphoribosyltransferase APRT. Genetic complementation and bioinformatics analysis revealed that the presence of wild type rbsR and apt inhibited xylose uptake or utilisation, while ptsI and ptsG might play a role in the regulation of CCR in P. thermoglucosidasius DSM 2542.